Genetic epidemiology of amyotrophic lateral sclerosis: a systematic review and meta-analysis. Issue 7 (5th January 2017) - Zou, Zhang-Yu; Zhou, Zhi-Rui; Che, Chun-Hui; Liu, Chang-Yun; He, Rao-Li; Huang, Hua-Pin
Abstract : Background: Genetic studies have shown that C9orf72, SOD1, TARDBP and FUS are the most common mutated genes in amyotrophic lateral sclerosis (ALS). Here, we performed a meta-analysis to determine the mutation frequencies of these major ALS-related genes in patients with ALS. Methods: We performed an extensive literature research to identify all original articles reporting frequencies of C9orf72, SOD1, TARDBP and FUS mutations in ALS. The mutation frequency and effect size of each study were combined. Possible sources of heterogeneity across studies were determined by meta-regression, sensitivity analysis and subgroup analysis. Results: 111 studies were included in the meta-analysis. The overall pooled mutation frequencies of these major ALS-related genes were 47.7% in familial amyotrophic lateral sclerosis (FALS) and 5.2% in sporadic ALS (SALS). A significant difference was identified regarding the frequencies of mutations in major ALS genes between European and Asian patients. In European populations, the most common mutations were the C9orf72 repeat expansions (FALS 33.7%, SALS 5.1%), followed by SOD1 (FALS 14.8%, SALS 1.2%), TARDBP (FALS 4.2%, SALS 0.8%) and FUS mutations (FALS 2.8%, SALS 0.3%), while in Asian populations the most common mutations were SOD1 mutations (FALS 30.0%, SALS 1.5%), followed by FUS (FALS 6.4%, SALS 0.9%), C9orf72 (FALS 2.3%, SALS 0.3%) and TARDBP (FALS 1.5%, SALS 0.2%) mutations. Conclusions: These findings demonstrated that the genetic architecture of ALS in Asian populations is distinct from that in European populations, which need to be given appropriate consideration when performing genetic testing of patients with ALS.